Agricultural Food Supply Chain Resilience and Environmental Health: The Roles of Collaboration, Flexibility, And Agility - Wangke, Shinta Jeanette C.; Tumiwa, Johan Reineer; Tuegeh, Octavia Diana Monica; Paat, Franda Benedicta (Jurnal Ilmiah PLATAX, 2026)
Agricultural food supply chains are increasingly exposed to disruptions caused by climate change, market volatility, logistical bottlenecks, and operational uncertainty, with important implications for food continuity and environmental health. This study examines the roles of supply chain collaboration, supply chain flexibility, and supply chain agility in shaping agrifood supply chain robustness in the laying hen sector of North Sulawesi, Indonesia. A quantitative cross-sectional design was employed, and data were collected from 180 valid respondents involved in the laying hen supply chain between July and October 2025. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) to test both direct and indirect relationships among the latent constructs. The results show that supply chain collaboration and supply chain flexibility have significant positive direct effects on agrifood supply chain robustness. Supply chain agility also has a significant direct effect and emerges as the strongest predictor of robustness. In addition, agility significantly mediates the effects of collaboration and flexibility on robustness, indicating that coordinated relationships and adaptive structures become more effective when translated into rapid operational responses. These findings suggest that resilient agricultural food supply chains depend on the integration of collaboration, flexibility, and agility to maintain supply continuity, reduce disruption impacts, and support safer and more sustainable food systems. The study contributes to the literature on agrifood resilience by linking dynamic supply chain capabilities with broader concerns of environmental health and offers practical implications for agribusiness managers and policymakers in developing regions. Keywords: Agrifood supply chain; Environmental health; Laying hen industry; Supply chain agility; Supply chain resilience